Improving Safety and Reducing Clinical Errors in Anesthesia: Which Checklist Is Your Choice? - Alireza Babajani; Atiyeh Sadat Sajadi; Zahra Pirdadeh Beiranvand; Shaghayegh Taghizadeh; Parisa Moradimajd (Archives of Anesthesia and Critical Care)
The safety of the beating heart is a health service that means the absence of clinical errors during the implementation of health care. The period of anesthesia is identified as one of the most critical phases for patients requiring general anesthesia, carrying the potential for critical clinical errors that may have irreversible consequences. This study's main objective was to conduct a concise assessment of the anesthesia checklists utilized to enhance patient safety during general anesthesia procedures. To accomplish this, a comprehensive search was conducted using relevant keywords spanning from 1990 to 2023 across databases including PubMed, Springer, Google Scholar, Web of Science, Scopus, online libraries, and the Cochrane library. Initially, 188 studies were identified at the outset of the research, and among these, 13 studies that focused on the development of checklists for anesthesia safety were scrutinized. Included articles were reviewed separately and divided into 3 categories; Specific vs. Generalized Scope, Single-Stage vs. Multi-Stage, Single-Factor vs. Multi-Factor. According to the findings from these studies, the systematic and proper utilization of all available checklists can contribute to improved safety. However, due to the specialization of surgical procedures and the increasing emphasis on patient safety over the past decade, there has been a shift in the compilation of anesthesia checklists from being broad and general to becoming specific, transitioning from single-stage to multi-stage, and evolving from single-factor to multi-factor checklists.